A late pre‐Islamic bowl with Levantine‐inspired decoration from ed‐Dur (UAE) - Overlaet, Bruno; Yule, Paul (Arabian archaeology and epigraphy, 2018)
Around 1977 the British engineer Peter Hudson found a corroded copper alloy bowl during a walk c.100-150 m south‐east of the ed‐Dur fort in Umm al‐Qaiwain. Ed‐Dur is one of the largest and most extensively explored sites along the UAE Gulf coast. Its main occupation dates from the late first century BCE to the early second century CE (PIR, Période préislamique récente, C). After cleaning, the bowl showed profuse engraved and repoussé decoration. It is compared with Levantine bowls from Nimrud, with several unprovenanced "South Arabian" bowls and with excavated bowls from the UAE and Oman. Although the bowl's iconography copies familiar themes from Early Iron Age Levantine bowls, the data suggest a much later, local production. The bowl is attributed to the late pre‐Islamic period (PIR), phases A to C (third century BCE-early second century CE).